Bone Marrow Concentrate Does Not Improve Osseous Integration of Osteochondral Allograft Transplants in the Knee: A Comparative Magnetic Resonance Imaging Analysis. Issue 7 (30th July 2018) - Wang, Dean; Lin, Kenneth; Pais, Mollyann D.; Burge, Alissa; Williams, Riley J.
Objectives: Fresh osteochondral allograft transplantation (OCA), which transfers viable, mature hyaline cartilage and subchondral bone into full-thickness chondral defects, has demonstrated good long-term results in the knee. However, incomplete osseous trabecular integration of allograft bone with the host bone is correlated with inferior patient-reported outcomes (Williams et al, JBJS, 2007) and can lead to graft failure. As a result, augmentation of OCA with bone marrow aspirate concentrate (BMAC) has been hypothesized to improve osseous incorporation of the allograft compared to OCA alone. The purpose of this study was to compare the appearance of osseous integration at the host-graft junction on magnetic resonance imaging (MRI) in patients treated with BMAC+OCA versus patients treated with OCA alone. Methods: Between February 2013 and June 2016, 29 patients with full-thickness cartilage defects were treated with BMAC+OCA (n = 10) or OCA alone (n = 19) and followed prospectively with an MRI at approximately 12 months after surgery. Intraoperatively, bone marrow aspirate was harvested from the ipsilateral iliac crest (Magellan, Arteriocyte), and the allograft plug was soaked in BMAC prior to implantation. No patients received a concomitant meniscus allograft transplantation, realignment osteotomy, or anterior ligament reconstruction. Bone, cartilage, and ancillary features on postoperative MRI were assessed and graded using the Osteochondral Allograft MRI Scoring System (OCAMRISS) by a blinded musculoskeletal radiologist. This is a system that scores subchondral bone plate congruity, bone marrow signal intensity, osseous integration, and cystic changes of the graft and host-graft junction as part of the bone features assessment (Meric et al, Cartilage, 2015) (Table 1). Comparisons of demographic characteristics and OCAMRISS scores between groups were performed with the Mann-Whitney test. Results: The mean ages of the BMAC and control groups were 32.9 and 33.4 years, respectively (p = 0.95). Males comprised 60% of the BMAC group and 68% of the control group (p = 0.70). MRIs for the BMAC and control groups were obtained at a mean of 11.2 (range, 9-14) and 11.3 (range, 8-15) months after surgery, respectively (p = 0.87). Mean total OCAMRISS scores were not significantly different between groups (BMAC - 7.8, control - 8.0; p = 0.93). Furthermore, mean bone (BMAC - 2.3, control - 2.8; p = 0.22), cartilage (BMAC - 3.3, control - 3.0; p = 0.55), and ancillary (BMAC - 2.2, control - 2.3; p = 0.92) feature scores were not significantly different between groups. Imaging for 5 patients (50%) in the BMAC and 11 patients (59%) in the control groups (p = 0.71) demonstrated a persistent discernible cleft without crossing trabeculae at the host-graft junction (Figure 1). Almost all grafts (over 90%) demonstrated persistent subchondral marrow edema relative to the epiphyseal bone. Conclusion: The addition of autogenous BMAC to OCA did not enhance osseous integration and bony features at the host-graft junction compared to OCA alone at 12 months. Although more MRI follow-up of patients treated with BMAC+OCA is needed to confirm this finding, these results suggest that any augmentative biologic effect of BMAC for OCA, if one exists, is likely to be small. Table 1. Osteochondral Allograft Magnetic Reponance Imaging Scoring System (OCAMRISS) (adapted from Metric et al) MRI Feature MRI Score Bone Features 1. Subchondral bone plate congruity of graft and host-graft junction 0: Intract and flush; 1: Disrupted or not flush by >1 subchondral thickness 2. Subchondral bone marrow signal intensity of graft relative to epiphyseal bone 0: Normal; 1: Abnormal (bone marrow edema pattern or hypointensity on all sequences) 3. Osseous integration at host-graft junction 0: Crossing trabeculae; 1: Discernible cleft 4. Presence of cystic changes of graft and host-graft junction 0: Absent; 1: Present Cartilage Features 5. Cartilage signal of graft 0: Normal; 1: Altered intensity (either hypointense of hyperintense, but not fluid); 2: Fluid signal intensity on all sequences 6. Cartilage "fill" of graft (percentage of volume) 0: 76-100%; 1: 51-75% or >100%; 2: <50% 7. Cartilage edge integration at host-graft junction 0: No discernible boundary; 1: Discernible boundary; 2: Discernible fissure >1 mm 8. Cartilage surface congruity of graft and host-graft junction 0: Flush; 1: <50% offset of host cartilage; 2: >50% offset of host cartilage 9. Calcified cartilage integrity of graft 0: Intract, thin, and smooth; 1: Altered (disrupted, thickened or blurred) Ancillary Features 10. Opposing cartilage 0: Normal; 1: Abnormal (bone marrow edema pattern or hypointensity on all sequences) 11. Meniscal tears 0: Absent; 1: Present 12. Synovitis 0: Absent; 1: Present 13. Fad pad scarring 0: Absent; 1: Present Figure 1. Representative 12-month coronal and sagittal MRI sections in a (A, B) 20-year-old male, demonstrating crossing trabeculae and minimal subchondral marrow edema, and (C, D) 16-year-old-male, demonstrating discernible clefts at the host-graft junction and significant subchondral marrow edema. Both were treated with BMAC+OCA